SINERGITAS PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI DALAM PEMBANGUNAN KEPARIWISATAAN TAHUN 2016-2017 - Yetni Maiyuri; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The amount of tourism potential in Kuantan Singingi Regency is not in line with the management done by the Local Government in this case the Department of Tourism and Culture of Kuantan Singingi Regency in this case has not been able to encourage investors ie 3rd party or private to synergize in building tourism and the government is still minimal to do promotion through local / national media. Hence the underlying writer to know more and do research Synergy of Local Government of Kuantan Singingi Regency in Tourism Development Year 2016-2017.The purpose of this research is to know the synergy of local government with the private sector and society for the development of tourism in Kuantan Singingi regency. The method used is qualitative method. This research was conducted in Kuantan Singingi Regency. Primary data sources through data directly as well as secondary data sources. Data analysis technique is done by qualitative descriptive analysis. Currently the Local Government of Kuantan Singingi Regency has not implemented the concept of Sinergitas in Tourism Development in Kuantan Singingi Regency. Inadequate management of facilities and infrastructure resulted in the lack of tourist visits.The result of this research is the lack of budget for Tourism Department resulted in not optimal management of tourism development and still lack of interest of investor or third party to establish cooperation with Local Government in managing Tourism resulted the existing tourism object, still lacking in facilities and infrastructure and Synergy conducted by the Government to the community and the 3rd party to the Development of Tourism is still lacking so that the object of tourism can not be a sector of Local Revenue.Keywords: Synergy and Tourism Development